The Eurocentric "I" and the White Mask of Colonialism: The African "Other" in Joseph Conrad's Heart of Darkness - (:unkn) unknown (My University, 2019)
Eurocentrism is a philosophy which makes of the European "I" the only reference for any judgement and evaluation. Europeans consider themselves as the embodiment of good culture while the other, the colonized, the non-European, is the incarnation of brutishness and savagery. In other words, Otherness is an image built up by a referent, who is superior, and who decides about the nature of the other. Subsequently, the imagemaking of otherness is the representation of the person, who projects his mind into it. Eurocentrism legalizes power and legitimizes domination and makes them central for the sake of effectiveness. Moreover, hegemony gives to the colonizer the right and responsibility to civilize the colonized. Colonialist discourse tries to impress and to make the other think of himself as inferior; thus, he needs to be civilized, colonized and guided. To be an "Other" is, then, to be silenced and dependent because there is no open possibility for him to change or to reach the European, the referent. The self-justification of imperialism was an idea of conquest of other people to usurp their riches and lands. Conrad's background of Heart of Darkness stems from the Euro-centric documents that acknowledge the subjective illegal right to dominate Africa and to make its natives an "Other.
Keywords: African Research